(untitled) (Contemporary Journal of Social Science Review, 2025)
Objectives: About 1.5 million trans-people live in Pakistan but barriers to equal rights and career development opportunities for trans-people have remained persistent in our community. Because of widespread societal rejection, Hijras are vulnerable in Pakistan. Most of the time, these individuals are highly weak and isolated from society, and they are often despised by their own family members. Since trans-people are an important part of society, this qualitative study sought to identify psychosocial determinants that contribute to life satisfaction among trans-people. Methods: Data were collected from 110 Trans people, recruited through purposive sampling. Each participant shared their experiences in a single session during interviews that lasted 45 to 60 minutes and were videotaped and transcribed. The recording of patient interviews, which took a month to complete, was done utilizing a portable voice recorder. Results: The current study revealed two main categories: social and psychological determinants, which includes fourteen themes that contribute to life satisfaction. There are seven social determinants which includes an attitude of society, family support, friends’ role, family rejection, lack of enjoying equal rights, poor govt, policies, and stereotypes regarding themselves. Findings concluded seven psychological determinants which include self-perception, the role of religion, acceptance of them, attitude towards life, bound to this profession, harassment and torture, and living conditions. The findings highlight the significance of psychosocial variables which could make the possibility for increasing life satisfaction among them. Conclusion: The current study contributed to a better understanding of the determinants of trans-people life satisfaction, as well as the role of psychosocial determinants of improving trans-person’s life satisfaction. Simultaneously, a more precise measure of life satisfaction can help readers understand the pathway of improvement in the life satisfaction of transgender individuals.